Evaluation of different discharging methods on HVAC electret filter media. (15th August 2018) - Tang, Min; Thompson, Drew; Chen, Sheng-Chieh; Liang, Yun; Pui, David Y.H.
Abstract: Electret filters with electrostatic charges added on fibers are widely used in HVAC system of residential and commercial buildings to mitigate PM2.5 exposure in indoor environments. Filtration applications require the knowledge of minimum filtration efficiency of electret filters under worst condition. To determine the minimum efficiency, different electret discharging methods are used in test standards to eliminate electrostatic effects. This study evaluated the isopropanol (IPA) liquid discharging method in EN 779 and the IPA saturated vapor treatment in ISO 16890. It was found that although both IPA liquid immersion and saturated vapor treatment can significantly remove fiber charge, saturated vapor treatment showed better discharging performance. The charge density of media discharged by IPA liquid immersion and saturated vapor treatment were 2 μC/m 2 and 0 μC/m 2, respectively. It demonstrated that IPA saturated vapor treatment can completely remove fiber charge, while undesirable fiber charge occurred after being treated by IPA liquid due to interface electrification. The test results of unsaturated vapor treatment indicated that IPA in the phase of vapor was not capable of removing fiber charges. The fact that saturated vapor treatment was more effective than liquid immersion was due to the different discharging process. For saturated vapor treatment, vapor condensed on fiber surface and formed a liquid layer with thickness of 15 nm. This ultra-thin layer of IPA liquid can discharge the fiber charge completely without inducing extra charge after liquid evaporation. This study concluded that discharging method in ISO 16890 should be used in electret filter test. Highlights: Saturated IPA vapor treatment showed better discharging performance than liquid. Undesirable fiber charge occurred after being treated by IPA liquid. Condensed IPA vapor formed an ultra-thin layer to remove fiber charge completely. Discharging method in ISO 16890 should be used in electret filter test.